MgSO4 prophylaxis for obstetric reasons: Traditional solutions vs ready-made solutions (Annals of Medical Research, 2021)
Aim: Magnesium (Mg) is frequently used in obstetrics as an anticonvulsant and neuroprotection in daily practice. Although ready-made solutions are produced today, health care workers still prepare and use MgSO4 via traditional methods. We planned this study to investigate the possible benefits of using ready-made solutions. Material and Methods: The solution prepared by traditional methods was compared to a ready-made solution in terms of Mg amount, preparation duration and cost over time. Results: Ready-made solutions resulted in a more homogeneous infusion (386.98±25.30 vs 402.65±21.68), lower cost (6.86 vs 5.56) and less labor loss (1258 (min: 900 – max: 1500) vs 0 sec). Conclusions: This study, it does show that the use of a ready-made solution allows the patient to receive a more homogenous infusion of magnesium over time, and it is more financially profitable. The use of ready-made MgSO4 solution also prevents the loss of time in the labor force that would have been spent preparing the solution.Keywords: Magnesium; prophylaxis; traditional solutions; ready-made solutions.
Keywords: Magnesium; prophylaxis; traditional solutions; ready-made solutions.